2018
DOI: 10.1172/jci97696
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia unawareness in type 1 diabetes suppresses brain responses to hypoglycemia

Abstract: BACKGROUND. Among nondiabetic individuals, mild glucose decrements alter brain activity in regions linked to reward, motivation, and executive control. Whether these effects differ in type 1 diabetes mellitus (T1DM) patients with and without hypoglycemia awareness remains unclear. METHODS. RESULTS.Mild hypoglycemia in HC subjects altered activity in the caudate, insula, prefrontal cortex, and angular gyrus, whereas T1DM-Aware subjects showed no caudate and insula changes, but showed altered activation pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 68 publications
1
24
1
2
Order By: Relevance
“…The depth of hypoglycemia in the PET study may explain why there was a more extensive cortical response and why the thalamus was activated in both HA and IAH. Together, Dunn et al (11), the current study, and Hwang et al (12) have demonstrated regional CBF changes at various stages of hypoglycemia. Reduced activity was seen in the right lateral OFC in IAH compared with HA during hypoglycemia.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The depth of hypoglycemia in the PET study may explain why there was a more extensive cortical response and why the thalamus was activated in both HA and IAH. Together, Dunn et al (11), the current study, and Hwang et al (12) have demonstrated regional CBF changes at various stages of hypoglycemia. Reduced activity was seen in the right lateral OFC in IAH compared with HA during hypoglycemia.…”
Section: Discussionsupporting
confidence: 71%
“…*P , 0.05, **P , 0.005 for euglycemia vs. hypoglycemia; #P , 0.05, ##P , 0.005 for HA vs. IAH. participants was more extensive than that seen by Hwang et al (12), who described decreased activity in the OFC with no change in the DLPFC. This may reflect our stronger hypoglycemic stimulus of 47 mg/dL (2.6 mmol/L) versus 60 mg/dL (3.3 mmol/L) in the Hwang et al study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…У больных СД1 с сохранным распознаванием гипогликемии нарушается активация префронтальной коры и angular gyrus, а у больных с НРГ активность мозга во время гипогликемии не меняется. Выраженность реакции головного мозга ассоциирована с гормональным ответом на гипогликемию и выраженностью ее симптомов [33].…”
Section: нарушение адаптации головного мозга к низкому содержанию глюunclassified